Distribution and ecology of Dormice (Myoxidae) in Sicily: a preliminary account - Maurizio Sarà; Giulia Casamento (Hystrix, the Italian Journal of Mammalogy, 1995)
Abstract Three dormouse species are recorded in Sicily: Myoxus glis, Muscardinus avellanarius and Eliomys quercinus. Their distribution is mapped according to the 10 x 10 km squares of the UTM grid. Data were collected until May 1993, mostly coming from pellet analysis, and direct records (vocalization listening, museum specimens, field observations, literature, etc.). The Fat dormouse (5.3% of 10 x 10 km squares) and the Hazel dormouse (2.1%) are mainly localized within deciduous wooded areas like the beech forests and the hazel groves mixed with oaks and chestnuts of Nebrodi and Madonie. The Fat dormouse is also present in south-eastern Sicily (Monti Iblei) and on in Eolian island (Salina). The Garden dormouse shows the widest distribution (21.2%), ranging from sea level to the beech forests (1600 m a.s.1.). Dormice are rarely preyed upon by Owls in Sicily, generally forming less than 1.5% of the total prey, with the exception the Fat dormouse (5.3%). Other occasional predators, so far recorded, are the Red Fox (Vulpes vulpes) and the Lanner (Falco biarmicus). Hibernation regularly occurs at high altitudes, but seems to be absent or curtailed in the warm habitats below 500 m a.s.1. Riassunto Distribuzione ed ecologia dei Mioxidi in Sicilia: dati preliminari - Tre specie di Mioxidi vivono in Sicilia (Myoxus glis, Muscardinus avellanarius, Eliomys quercinus). Storicamente (1850) essi erano presenti nelle principali aree boscate (Nebrodi, Madonie, Etna), solo nella metà di questo secolo, il Ghiro ed il Quercino furono scoperti alle isole Eolie (Salina e Lipari). Si riporta la carta di distribuzione di ogni specie (griglia UTM, 100 kmq) ricavata dall'analisi della dieta di predatori, osservazioni dirette, trappolamenti ed esemplari citati in bibliografia o conservati nei musei. Il Ghiro (5,3%) ed il Moscardino (2,1%) sono localizzati nei boschi decidui di querce e faggio e, più in basso di noccioli, querce e castagni dei Nebrodi, Peloritani e Madonie. Il Ghiro è presente anche sull'Etna ed in un'area meridionale della Sicilia (Iblei). Il Quercino mostra la distribuzione più ampia (21,2%) ed è presente in una gran varietà di habitat dal livello del mare fino alle faggete delle Madonie. I Mioxidi in Sicilia risultano predati finora occasionalmente dalla Volpe e dal Lanario e raramente dal Barbagianni e dall'Allocco. Solo il Ghiro risulta predato regolarmente (5%) dall'Allocco e risulta la preda più importante in termini di biomassa (47%) nei boschi dell'Etna e dei Nebrodi. Il periodo di letargo, desunto da osservazioni dirette e dalle borre, sembrerebbe normale (autunno inoltrato-primavera) alle alte quote e assente o molto ridotto e discontinuo sotto i 400 m.